Nucleophilic Etching Growth of Zeolite Materials with High Tunability. Issue 24 (21st November 2021) - Dong, Lei; Chen, Yanpeng; Wang, Ya; Wang, Yanding; Gao, Jinqiang; Zhu, Rongshu; Hong, Mei; Yang, Shihe
Abstract: Etching growth is widely employed for growing metal species, carving out some of the finest nanocrystals. However, such a general concept has so far evaded the growth of porous crystals. Herein, a novel nucleophilic etching growth mechanism that can be exploited to tune zeolite materials is uncovered. Most critical is the identification of mild etchant used in situ to successfully synthesize high‐quality hierarchically porous ZSM‐5 crystals. Time‐series sample characterizations allow to visualize and track the complex zeolite crystallization pathway involving initial nucleation, intermediate dissolution, and subsequent nanoparticle attachment regrowth. Competition and cooperation between framework growth and in situ dissolution lead to facile control over size, morphology, crystallinity, composition, and mesoporosity by varying the amount of etchant or nucleophilicity. The judicious use of this mechanism results in dramatically improved catalytic activity in methanol to hydrocarbon reactions owing to the simultaneously increased crystallinity, secondary mesopores, and proper acid properties. Abstract : A dynamic equilibrium between nucleophilic etching and framework growth allows control over size, composition, morphology, crystallinity, mesoporosity, and catalytic performance of ZSM‐5 zeolites, which greatly improves catalyst lifetime and selectivity in methanol to hydrocarbon reactions, giving rise to high turnover number of 1.5 × 10 6 under the high methanol feed rate with weight hourly space velocity of 12 gMeOH gcatalyst −1 h −1 .